1993
DOI: 10.1515/humr.1993.6.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Sex and salience in the appreciation of cartoon humor

Abstract: In two related experiments cartoons were selectedas high or low in sexuality and high or low in rated humor. Matched sets of these cartoons were presented to prime a specific humor context thenfollowed by a different sei with characteristics that contrasted with the first. The participants, 265 females and 171 males in the first study and 311 females and 243 males in the second study, judged the funniness of the cartoons on a scale from 0 (not funny at all) to 20 (one of the funniest ever seen). Humor ratings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 17 publications
0
23
1
Order By: Relevance
“…The ANOVA here followed the same format äs for comprehension difficulty. With relatively non-sexual aggressive cartoons and the sexual materials that deprecate females incorporated into incongruity resolution, the gender difference found previously on similar material was not significant here, F(l,22) = 1.27,/?>0.25 (Derks 1992;Derks and Arora 1993). Therefore the amusement ratings were also collapsed over participant gender.…”
Section: Resultsmentioning
confidence: 57%
“…The ANOVA here followed the same format äs for comprehension difficulty. With relatively non-sexual aggressive cartoons and the sexual materials that deprecate females incorporated into incongruity resolution, the gender difference found previously on similar material was not significant here, F(l,22) = 1.27,/?>0.25 (Derks 1992;Derks and Arora 1993). Therefore the amusement ratings were also collapsed over participant gender.…”
Section: Resultsmentioning
confidence: 57%
“…For example, making the punch line more incongruous simultaneously means changing its content or other properties. One way out is, for example, to leave the jokes intact, but undertake a differential priming of the two meanings of a key word in a joke (Wilson, 1979), or a priming of the theme (Goldstein, Suls & Anthony, 1972) or even the structure (Derks & Arora, 1993) of the jokes to follow.…”
Section: Traditional and Nontraditional Vehicles For Transporting Funmentioning
confidence: 99%
“…The finding that males have a significantly more favourable view of the cartoon Beavis & Butthead than females, was as expected though the significant differences found for Roadrunner and The Simpsons were a surprise. Expectations with regard to Beavis & Butthead were founded both on personal observations, casual conversation, and on the afore mentioned studies by Derks and Arora (1993) and Hemmasi et al (1994). The humour in the cartoon comes almost entirely from sexist behaviour and language and from toilet-humour, and these earlier studies have shown that females appreciate this type of humour less often than males.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is suggested. Derks, P. & Arora, S. (1993). Sex and salience in the appreciation of cartoon humor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation